Learn English With Artificial Intelligence (Sosialisasi Pemanfaatan Teknologi Kecerdasan Buatan (AI) dalam Belajar Bahasa Inggris) - Yeni Daniarti; Sri Mulyati; Syepry Maulana Husain; Ilham Pratama (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2024)
The community service activity "Learn English With Artificial Intelligence" at Islamic Village Vocational School, led by lecturers from the Informatics Engineering Study Program, Faculty of Engineering, Muhammadiyah University of Tangerang (UMT), aims to integrate artificial intelligence (AI) technology in English language learning. This activity succeeded in increasing understanding of the concept of AI and its benefits in education, motivating students to study English more intensely, and increasing the effectiveness of learning through AI applications such as Duolingo and Grammarly. provide regular training for teachers, encourage collaboration between schools, and conduct further research to measure the long-term impact of using AI in education. Thus, the success of this activity is not only in achieving the set educational goals, but also in expanding the boundaries of innovation in ways of learning English and the potential for further development in the increasingly connected and digital context of modern education. supporting education at the Islamic Village Vocational School.